"TYPES OF REAL RIGHTS IN THE REPUBLIC OF NORTH MACEDONIA, BEFORE AND AFTER THE ADOPTION OF THE LAW ON OWNERSHIP AND OTHER REAL RIGHTS." (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The focus in this paper is placed initially on the conceptual determination of real rights (property rights) and real legal relations, with special emphasis on the development course of real legal relations in the Republic of North Macedonia before and after the adoption of the Law on ownership and other real rights.Before the adoption of this law, various regulations were in force in the RNM, which prescribed the rules for the regulation of real legal relations, which were valid for the countries of the former SFRY and so on.By processing the available legal regulations, and by consulting domestic and foreign literature and regulations, the purpose of this paper is to provide a comparative and content analysis of the legal regulations in the area of real law as well as to compare them with today's positive regulations in the RNM.Through the comparative analysis, insight is provided into the solutions of other countries in the area of property relations, which enables in the future some of the innovative solutions contained in them to be incorporated into the Civil Code of the RNM, which will represent one of the biggest turning points and challenges in the development of the legal science and the legal order in RNM and will enable greater legal certainty in general.